Pembuatan Media Promosi Dalam Bentuk Desain Kemasan Menggunakan Aplikasi Canva Pada UPPKS Sumber Rahayu Tumpang Kabupaten Malang - Elsa Sugandy; Umi Khabibah (Jurnal Ekonomi dan Bisnis Digital, 2025)
This research has an aim to create promotional media in the form of effective packaging design with Canva application. The method used in this research is Action Research with research procedures consisting of planning, action, observation and reflection. The data collection was conducted with observation, interviews, documentation, and questionnaires. The questionnaires were distributed to 15 respondents consisting of 1 business pemilik, 2 graphic design experts, 2 marketing experts, and 10 potential consumers. The method for measuring of effectiveness used the EPIC Model (Empathy, Persuasion, Impact, Communication). The analysis results after improvements showed an average EPIC Rate of 4.52, indicating that the packaging design is very effective and suitable for use. Based on the results of the research, it can be concluded that the created packaging design is very effective and suitable for use as a promotional media through packaging design. Thus, it is recommended that Sumber Rahayu use attractive, informative, and innovative packaging designs that can compete with other products in the market.